Enhanced Biocompatibility of Multi-Layered, 3D Bio-Printed Artificial Vessels Composed of Autologous Mesenchymal Stem Cells - Jang, Eui Hwa (Polymers (Basel), 2020)
Artificial vessels capable of long-term patency are essential clinical tools in vascular surgery that involves small vessels. On-going attempts to develop artificial vessels that complements restenosis have not been entirely successful. Here, we report on the fabrication of small-sized artificial vessels using a three-dimensional bio-printer. The fabrication employed biodegradable polycaprolactone and autologous MSCs harvested from the bone-marrow of canines. The MSCs were cultured and differentiated into endothelial-like cells. After confirming differentiation, artificial vessels comprising three-layers were constructed and implanted into the arteries of canines. The autologous MSCs printed on artificial vessels (cell-derived group) maintained a 64.3% patency (9 of 14 grafts) compared with artificial vessels without cells (control group, 54.5% patency (6 of 11 grafts)). The cell-derived vessels (61.9 cells/mm(2) ± 14.3) had more endothelial cells on their inner surfaces than the control vessels (21 cells/mm(2) ± 11.3). Moreover, the control vessels showed acute inflammation on the porous structures of the implanted artificial vessels, whereas the cell-derived vessels exhibited fibrinous clots with little to no inflammation. We concluded that the minimal rejection of these artificial vessels by the immune system was due to the use of autologous MSCs. We anticipate that this study will be of value in the field of tissue-engineering in clinical practice.